CINNAMON ROLL MILLET (Ciromill) Sweet Bread Made From Millet Flour As A High-Protein Dessert - Sugiyono, Muhammad Ndaru Cahyo Sumirat (Prosiding Pendidikan Teknik Boga Busana, 2020)
This study aims to 1) find the exact formula of cinnamon roll products substituted for millet flour.2) to find out public acceptance of cinnamon roll products substituted for millet flour. However, the general aim of this research is to increase local food consumption through the innovation of cinnamon roll products substituted for millet flour to emphasize the need for wheat flour in Indonesia. In the research and development procedure, this study uses the ADDIE model which is combined with the 4D model to produce Analysis (reference product studies), Design (product design), Develop (product manufacture and testing) and Disemination (product exhibition). The subjects of this study were residents of PTBB FT UNY and the community at large. This research was conducted in the Chemistry Laboratory Building, Department of Culinary Engineering, with time allocation, from January 2019 to May 2019. Data collection was conducted to find out whether the product results were acceptable or not by the community. Data collection methods carried out by using product acceptance tests. Then the data from the product testing are analyzed descriptively and quantitatively. The results of study 1) the determination of the exact formula of cinnamon roll products substituted for millet flour.2) the results of the T test value between control and development were not significantly different, meaning that this product could be accepted. 3) the value of community acceptance of cinnamon roll substitution of millet flour at 3.75 with light is very preferred. The data shows that this substitution product is accepted by the community. Keywords: High Protein, Millet Flour, Development, Utilization, Nutritional Test